ЭРТАК ТИП СЮЖЕТЛИ ДОСТОНЛАРНИНГ ЖАНРИЙ ХУСУСИЯТЛАРИ («Шаҳриёр», «Шийрин-Шекер», «Қаншайым», «Муңлық - Зарлық», «Тулым бий», «Жәҳәнша» достонлари мисолида ) - Кенесбаева, Ш.К. (SCIENCE and SOCIETY, 2022)
The article analyzes the fact that fairy-tale epics such as "Shahriyor", "Shiyryn Sheker", "Qanshayym", "Munlyq - Zarlyq" are a new aesthetic system, in terms of genre, but in terms of creativity. The article also examines the epic "Amanbay batyr" from this point of view.